Kinetics of hydrogen permeation through W-Pd bimetallic systems - Glazunov, G.P.; Andreev, A.A.; Baron, D.I.; Volkov, E.D.; Causey, R.A.; Hassanein, A.; Kitaevskiy, K.M.; Konotopskiy, A.L.; Lapshin, V.I.; Neklyudov, I.M.; Patokin, A.P. (Вопросы атомной науки и техники, 2005)
The experimental investigations had been carried out of the kinetics of hydrogen permeation through W-Pd bimetallic systems. The possible mechanisms had been suggested and analyzed to explain the observed anomalies in the hydrogen permeation behavior of such systems, on the assumption of measured isotherms and isobars of hydrogen permeability, energy state of hydrogen in W-Pd system, and theory of hydrogen diffusion in the systems, which contains large number of closed and interconnecting pores Проведено експериментальні дослідження кінетики проникнення водню через W-Pd біметалічні системи. Запропоновано можливі механізми для пояснення виявлених аномалій у поводженні воднепроникнення таких систем, виходячи з обмірюваних ізотерм і ізобар проникнення водню, енергетичного стану водню в системі W-Pd і теорії дифузії в системах з великою кількістю замкнутих і сполучених пор. Проведены экспериментальные исследования кинетики проникновения водорода через W-Pd биметаллические системы. Предложены возможные механизмы для объяснения обнаруженных аномалий в поведении водородопроницаемости таких систем, исходя из измеренных изотерм и изобар водородопроницаемости, энергетического состояния водорода в системе W-Pd и теории диффузии в системах с большим количеством замкнутых и сообщающихся пор.